Asking the Right Questions: A Framework for Developing Gender-Balanced Political Knowledge Batteries. (March 2023) - Kraft, Patrick W.; Dolan, Kathleen
Gender differences in political knowledge are a well-known empirical finding in public opinion research. Scholars working in this area have proposed various explanations for this phenomenon, often focusing on issues regarding the format and content of factual knowledge batteries. Yet, there are surprisingly few works that focus on how scholars might diversify the content of political knowledge measures to develop items that are less biased toward male areas of expertise. In this paper, we propose an inductive framework to develop more gender-balanced knowledge batteries by including political issues that are of particular relevance to women and women's lives. Employing gender-balanced measures of political knowledge reveal instances where women and men demonstrate equivalent levels of political knowledge and higher levels of political interest and efficacy among women—engagement that is often masked by conventional measures of knowledge.